2022
DOI: 10.1371/journal.pone.0277564
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin (stx) encoding genes in sheep and goats reared in Trinidad and Tobago

Abstract: Shiga toxin-producing Escherichia coli (STEC) is estimated to cause over two million cases of human disease annually. Trinidad and Tobago is one of the largest livestock producer and consumer of sheep and goat meat in the Caribbean, however, the potential role of these animals in the epidemiology of STEC infections has not been previously described. To fill this critical gap in knowledge, the prevalence of Shiga toxin genes (stx1 and stx2) shed in the faeces of healthy sheep (n = 204) and goats (n = 105) in Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Other studies conducted in countries such as Ireland [125], Iran [127], Norway [126], Spain [128], New Zealand [129], Australia [130], the United States [131], and Brazil [132] have also reported high STEC prevalences in sheep populations worldwide, ranging from 45% to as high as 87.6%. Conversely, comparatively fewer studies have reported low STEC prevalences in sheep populations, ranging between 32~36% [120,133,134].…”
Section: Sheepmentioning
confidence: 97%
See 2 more Smart Citations
“…Other studies conducted in countries such as Ireland [125], Iran [127], Norway [126], Spain [128], New Zealand [129], Australia [130], the United States [131], and Brazil [132] have also reported high STEC prevalences in sheep populations worldwide, ranging from 45% to as high as 87.6%. Conversely, comparatively fewer studies have reported low STEC prevalences in sheep populations, ranging between 32~36% [120,133,134].…”
Section: Sheepmentioning
confidence: 97%
“…While there does not appear to be an identifiable pattern of distribution of stx1and stx2-positive STEC strains within cattle populations, the STEC strains that colonize sheep appear to be more likely to be positive for stx1 than stx2. For example, Persad et al [134] found that, among 453 sheep STEC strains, 71% were positive for stx1 only, compared with the 11% that were stx2-positive only and the 18% that were positive for both. Similarly, Sánchez et al [128] found that the proportion of stx1-postive STEC strains (52.8%) from sheep was markedly greater than that for stx2-positive strains (8.4%), though a significant proportion of isolates (38.8%) were found to harbor both stx1 and stx2 genes.…”
Section: Sheepmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, all enterohemorrhagic E. coli strains found in animals are considered a risk to humans. However, serotype O157 can cause disease in humans and does not pose a risk to adult animals (7). The virulence factors of E. coli O157:H7, including toxins, adhesins, hemolysin, lipopolysaccharide, and flagellum, significantly contribute to the low infectious dose of this bacterium (8).…”
Section: Introductionmentioning
confidence: 99%